Pemodelan Karakteristik Hidro Oseanografi Di Wilayah Perairan Pantai Tanah Hitam, Kecamatan Paloh, Kabupaten Sambas, Menggunakan Software Mike 21 - Sutarno, Ainur Rohmah; Lestari, Arfena Deah; Danial, Mochammad Meddy (Jurnal Laot Ilmu Kelautan, 2024)
The coastal waters of Tanah Hitam are located in the village of Tanah Hitam, south of Paloh District. One of the issues occurring in this area is the coastline changes due to erosion and accretion. The exact factors causing these phenomena are not yet known, hence this research is conducted. This study examines hydro-oceanographic aspects of the coastline. The method used involves modeling tidal fluctuations, wind, currents, and waves using Mike 21 software. Data utilized in this research include bathymetric data, tidal data, and wind data obtained from BATNAS, SRGI, and Copernicus respectively. The results of the bathymetric modeling indicate depths ranging from 0 to 35 meters in the waters. The wind rose modeling results for the year 2022 show dominant winds blowing from the North at 13% frequency with speeds ranging from 1.5 to 7.5 m/s. Tidal current modeling for the year 2022 indicates that during high tide conditions, the highest velocity occurs in April at 0.280 m/s, predominantly flowing towards the East and Southeast. Conversely, during low tide conditions, the highest velocity occurs in February at 0.225 m/s, flowing towards the West. The highest maximum wave occurs in August and December, reaching heights of up to 1.500 meters. The highest significant wave occurs in August and December, with a height of 0.750 meters. Analysis of the tidal current modeling reveals that the movement of tidal currents contributes to the erosion and accretion of the Tanah Hitam coastline, primarily due to variations in water depth around it. Meanwhile, wave modeling analysis indicates that waves propagating towards the coast can generate alongshore currents due to wave breaking, which significantly influences sediment distribution, thereby affecting changes in the Tanah Hitam coastline.